Gestion de infraestructura vial (EDICIONES UC, 2018)
Road infrastructure management is a civil engineering discipline that allows objectively diagnosing, evaluating, planning and programming the maintenance of road assets throughout their useful life, optimizing the use of available resources. The main objective of this book is to contribute to the training of undergraduate and postgraduate students, and to support the work of the public sector in ministries, services, municipalities, among others, and also of the private sector in concessionaires, construction companies, investors, consultants, etc. among others. The main contents are: systems engineering concepts used in road infrastructure management; technical evaluation of road infrastructure; behavioral models; future maintenance needs; economic evaluation of projects; and infrastructure management applications, such as concessions, road safety, bridges and airports. This third corrected and expanded edition incorporates the latest research in the area and addresses new key aspects, such as the management of risk presence, urban pavements, roads low-volume traffic and road assets, among many others. Without a doubt, this work will once again become an essential book for students, academics, and professionals in the public and private sectors who need to be up-to-date in this important area of ​​development.